Human Resource Strategy Management In Industrial Relations Or Labor (Case Study: Analysis Of Human Resource Needs And Industrial Relations Management For Administrative Employees At Bandung Kiwari Regional Hospital) - Tanya ananda syafira; Aprinawati; Muhammad reza syahputra; Kasah Sigalingging; Ridho Rizkillah (Jurnal Multidisiplin Sahombu, 2024)
A healthy relationship between management and workers is the key to creating a productive and minimally conflicted work environment. Effective management not only focuses on achieving business targets, but must also ensure that workers feel motivated, involved in decision-making, and given space to grow. Open, collaborative communication, and a fair reward system can increase employee loyalty and motivation, which ultimately has a positive impact on company performance. RSUD Bandung Kiwari is one of the regional public hospitals that serves the community with various health services. As a hospital that provides various medical services, the operational success of the hospital is highly dependent on the existence of competent human resources (HR) and effective industrial relations management, especially in the administration sector. This study aims to determine the Strategic Management of Human Resources Industrial Relations or Employment (Case Study: Analysis of Human Resource Needs and Industrial Relations Management in Employee Administration at RSUD Bandung Kiwari). The method used is qualitative. The results of this study are Increasing the number of employees, qualifications, and improving industrial management relations will have a positive impact on employee productivity and the quality of hospital services.